MINDFUL WORDS IN DIGITAL SPHERE: A BUDDHIST APPROACH TO ETHICAL COMMUNICATION IN SOCIAL MEDIA - Abhishek Srivastava 1, Dr. Umesh Kumar Saxena 2 (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
The most advance form of communication with instant dissemination of messages and obsequious nature of social media, not only give it popularity but makes us open dared, cautious and concerned due to the challenges we heard and encounter in our daily life. Acting as a cosmos of information it also contains demerits like misinformation, fake-news, cyber bullying, trolling, privacy concern, online abuse, harassment and mental health etc. To overcome these challenges media literacy is one of the effective tools for the user to consume the digital space and social media platform as a boon of digital felicity. According to Indian rhetoric and communication practicing the Buddhist philosophy seeks the values of truthfulness, compassion and conciliation by its noble eight folded path of ethics in communication comprises with mutuality, open-mindedness, honesty, and respect. Here by studying the Buddhist philosophy we come to understand model of communication. This study will insight that how by following the Buddhist approach in digital sphere will make the social media legitimately viable to use.